EMPATHY AGAINST DISGUST: AN INTERPRETIVE PHENOMENOLOGICAL ANALYSIS OF HEALTHCARE PROFESSIONALS' EXPERIENCES OF CARING FOR PALLIATIVE PATIENTS WITH DISGUSTING SYMPTOMS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Muggleton, Joshua; Guy, Helen; Howard, Ruth
Abstract : Background: Disgusting symptoms are common in healthcare settings. Previous research has identified that healthcare professionals systematically avoid contact with patients with disgusting symptoms (Kray, 2004) potentially compromising patient care. Furthermore, Whitby and Gracias (2013) highlighted disgust in healthcare professionals as a possible contributory factor to dehumanization, and the abuses documented in the recent Francis report (Francis, 2013). Disgust may also have a detrimental effect on the wellbeing of healthcare professionals. Given that showing disgust is thought to be unprofessional (Holmes, Perron and O'Byrne, 2006) healthcare professionals may feel unable to express or process disgust in their work. The suppression of emotions, such as disgust, has been associated with poorer emotional health (Gross and Oliver, 2003). Therefore, healthcare professionals may be at risk of developing long-term emotional difficulties, or burning out. Aim: Given the ubiquity of disgust in palliative care (MacLeod, 2011), we investigated how palliative healthcare professionals' experience and cope with disgust in their work, and how they are supported in doing so. Methods: We interviewed six palliative healthcare professionals and analysed their transcripts using Interpretive Phenomenological Analysis (Smith, 1996) Analysis: Fifteen themes were identified and explored. These included the importance of being an empathetic professional, that disgust damages relationships with patients, and that staff talk about 'difficulties', not disgust . Conclusions: Three key findings emerged. Firstly, participants were uncomfortable talking about disgust at work, and were unable to access support for disgust. Secondly, in focusing on their patient's needs, participants often neglected their own emotional needs. As a result, it appeared that some participants projected their own emotions onto their patients, or else linked their own emotional wellbeing to the wellbeing of their patients. Finally, participants were at risk of reducing vital socio-emotional support for patients with disgusting symptoms. Based on our analysis, we suggest interventions to counteract these effects.